Conditional Pop-up Reminders Reduce Incidence of Rounding in Web Surveys. Issue 4 (November 2022) - Schnell, Rainer; Redlich, Sarah; Göritz, Anja S.
Frequency of behaviors or amounts of variables of interest are essential topics in many surveys. The use of heuristics might cause rounded answers, resulting in the increased occurrence of end-digits (called heaping or digit-preference). For web surveys (or CASI), we propose using a conditional prompt as input validation if digits indicating heaping are entered. We report an experiment, where respondents in an online access panel ( n = 2, 590) were randomly assigned to one of three groups: (1) no input validation; (2) conditional input validation if rounding was presumed; and (3) input validation every time a numerical value was entered. Conditional input validation reduces heaping for variables with high proportions of heaped values. Unconditional input validation seems to be less effective.